Adenoid cystic carcinoma of the breast, from diagnosis to management: a case report - Mendoza-Urbano Diana Marcela; Cañon Diana; Palazuelos Gloria Ines; Torres Fabio; Wills Beatriz; Rodriguez-Urrego Paula Andrea (Journal of Medical Case Reports)
Abstract Background Adenoid cystic carcinoma of the breast is a rare subtype, constituting less than 3.5% of primary breast carcinomas. Despite being categorized as a type of triple-negative breast cancer, it generally has a favorable prognosis. The primary management approach typically involves breast-conserving surgery. Due to its rarity, diagnosis can be challenging, emphasizing the importance of histopathological confirmation with clinical and imaging correlation. Although this tumor often has a favorable prognosis, additional research is necessary to better understand its clinical, radiological, and pathological features. Case presentation We present the case of a 54-year-old Colombian woman of Hispanic ethnicity who had a lesion detected by mammography at the junction of the upper quadrants. Breast ultrasound revealed a Breast Imaging Reporting & Data System category 5 solid nodule, 0.8 × 0.7 cm, with irregular borders in the left breast and no axillary abnormalities. A biopsy confirmed infiltrating carcinoma with tubular and cribriform patterns. Immunohistochemistry was consistent with adenoid cystic carcinoma of the breast (triple-negative). Contrast-enhanced breast magnetic resonance imaging showed a primary tumor measuring 18 × 11 × 15 mm at the upper quadrant interface, along with another suspicious mass measuring 50 × 10 mm in the retroareolar region, as well as multiple adjacent enhancing foci suggestive of multicentric tumor involvement with probable ductal extension. Due to potential multifocality, the patient underwent a nipple-sparing mastectomy and sentinel node dissection. Pathology revealed a unifocal retroareolar adenoid cystic carcinoma measuring 2.5 mm, situated less than 1 mm from the deep surgical margin and with a positive anterior margin. There was no evidence of lymphovascular or perineural invasion. The final diagnosis was triple-negative adenoid cystic carcinoma, classic subtype. A multidisciplinary board recommended radiotherapy and imaging follow-up. Postoperative outcomes remained satisfactory during follow-up with the breast surgeon. Conclusion This case report aims to raise awareness within the medical community regarding this rare cancer, highlighting the importance of accurate clinicopathological recognition and diagnosis. Multidisciplinary management remains crucial as the cornerstone of care, especially for offering therapies tailored to each patient’s specific needs.